Folklore and tradition in ethnomusicology : a comparison of their use and meaning in Italian and Croatian through English - Cimardi, Linda (Array, 2019)
The terms folklore and tradition (and the derived adjectives) in relation to music have been employed to define the subject of ethnomusicologists’ study. In this article, the meaning of these words is considered in their historical use in ethnomusicology and akin disciplines, as well as in the common sense in English, Italian and Croatian, trying to identify the main shared elements as well as the differences. While folklore is a word of foreign origin integrated in several languages, where it assumes diverse connotations also in terms of esthetical and moral value, the related adjective folk has local equivalents in Italian (popolare) and Croatian (narodni), which have been employed with reference to national musical expressions. Tradition is semantically partly overlapping with folklore, and in recent years the derived adjectives (tradicionalan, tradicijski) have been preferred in Croatian, while in Italian the word traditional (tradizionale) can be used to refer to non-European musics, and in general the locution musiche di tradizione orale is today favoured to define the subject of ethnomusicology. It appears that the national use of these words has marked their local understanding, as well as the related scholarship, and thus a reflection on the use of English in present academic and non-academic contexts is necessary.